Growth modification treatment of mandibular retrognathism using twin block apparatus (case report): Perawatan modifikasi pertumbuhan pada kondisi retrognati mandibula menggunakan peranti twin block (laporan kasus) - Chrisni Oktavia Jusup; Endah Mardiati (Makassar Dental Journal, 2022)
Interceptive orthodontic treatment, which is growth modification treatment using removable appliances such as twin block, is effective in treating skeletal retrognathic mandibular abnormalities in growing patients. A 10-year-old female with class II den-toskeletal malocclusion with retrognathic mandibular was treated using a twin block device for 8 months of active period and 4 months of retention period to obtain class I skeletal relationships, class I molar and canine relationships and normal overjet and overbite. Treatment begins with recording the bite by instructing the patient to advance her lower jaw as needed, then ma-king a twin block tool design. Devices with maxillary and mandibular bite blocks are worn for at least 20 hours a day with con-trol intervals every 2 weeks. The treatment results were very good with the patient's skeletal relationship being class I. It was concluded that patients with retrognathic mandibular can be treated by growth modification using the twin block device, with good patient cooperation, this tool effectively stimulates mandibular growth.